2018
DOI: 10.1021/acs.energyfuels.8b00792
|View full text |Cite
|
Sign up to set email alerts
|

High Density Alkyl Diamondoid Fuels Synthesized by Catalytic Cracking of Alkanes in the Presence of Adamantane

Abstract: Alkyl diamondoid fuel mixtures have been prepared under moderate conditions by AlBr3 catalyzed cracking of nonane and heptane in the presence of adamantane. The fuel mixture prepared with heptane as the alkyl source (HA) contains primarily 1-ethyl-3-methyl adamantane and 1-propyladamantane, while the mixture prepared from nonane (NA) contains primarily C13–C15 alkyl diamondoids. Both fuel mixtures exhibit densities greater than 0.9 g/mL and volumetric net heats of combustion approximately 10 and 6% higher than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…A more direct comparison with representative C 16 cycloalkanes is not currently viable, given the lack of literature data. However, recent work has shown that C 12 -C 15 alkyl diamondoids (highly branched multicyclic alkanes with fused cyclohexane ring systems and short alkyl chains) have reported DCNs ranging from 43 to 49, suggesting that cyclohexane ring systems do not have a significant negative impact on the DCN of parent hydrocarbons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A more direct comparison with representative C 16 cycloalkanes is not currently viable, given the lack of literature data. However, recent work has shown that C 12 -C 15 alkyl diamondoids (highly branched multicyclic alkanes with fused cyclohexane ring systems and short alkyl chains) have reported DCNs ranging from 43 to 49, suggesting that cyclohexane ring systems do not have a significant negative impact on the DCN of parent hydrocarbons.…”
Section: Resultsmentioning
confidence: 99%
“…One route to improve the density of renewable diesel fuel is to focus on the synthesis of cycloalkanes (naphthenes) instead of linear and branched alkanes. Although most cycloalkanes have low to moderate cetane numbers, the incorporation of modest length alkyl chains can enhance the cetane number and allow for the isolation of full performance fuels. A straightforward and atom-economic route to cycloalkane synthesis is through [4 + 2] Diels–Alder cycloaddition, suggesting that a sustainable conjugated diene derived from a renewable source would be an ideal substrate.…”
Section: Introductionmentioning
confidence: 99%
“…It should be especially noted that in recent years, the researchers have widely studied alkyl derivatives of diamondoids, including penta- and hexacyclotetradecane, due to their unique properties, such as high density, thermal stability, high calorific value, and good low-temperature characteristics, which make them promising as high-energy rocket fuels. …”
Section: Introductionmentioning
confidence: 99%
“…High-energy-density hydrocarbon fuels have relative high density and volumetric energy content; so, these kinds of fuels are very attractive. , High-energy-density hydrocarbon fuels are critical for volume-limited aircraft to increase the effective load and extend the flight range . It has been reported that adamantane fuels derived from some reservoirs exhibit a high density and volumetric heating value, and they are regarded as one new kind of high-energy-density hydrocarbon fuel.…”
Section: Introductionmentioning
confidence: 99%